The dead take the A Train - Khaw, Cassandra; Kadrey, Richard (Carrion City, 2023)
"Julie is a coked-up, burnt-out thirty-year-old whose only retirement plan is dying early. She's been trying to establish herself in the NYC magic scene, and she'll work the most gruesome gigs, exorcize the nastiest demons, and make deals with the cruelest gods to claw her way to the top. But nothing can prepare her for the toughest job yet: when her best friend, Sarah, shows up at her door in need of help. Keeping Sarah safe becomes top priority. Julie is desperate for a quick fix to break the dead-end grind and save her friend. But her power grab sets off a deadly chain of events that puts Sarah - and the entire world - directly in the path of annihilation."--